Grand finale? : a conclusão do ensino médio no colégio estadual Cândido José de Godói (Porto Alegre/RS, 2014) - Silva, Bárbara Virgínia Groff da (2015)
This dissertation examines the high school graduation in 2014 from the State College Cândido José de Godói, located in Porto Alegre (RS, Brazil). The objectives of this research are twofold: investigate the importance of high school graduation for young students of the diurnal third year of the educational institution in question, in order to identify who would be these young people and what the reasons leading them to consider important this rite of passage. The other goal seeks to contextualize the Brazilian high school throughout the twentieth century as a way to understand how this level of education was organized, such as its recent transformations and challenges related to this educational stage. This research is linked to the History of Education as it analyzes the historical trajectories of the high school, the neighborhood where the school is located as well as the paths that the College Godói ran along its decades of existence. In addition, the former graduations from the educational institution were investigated from the vestiges located in history archive of the College Godói. In this part of the dissertation, concepts such as school culture and school's rite are used. Regarding the graduation of 2014, has crafted a questionnaire answered voluntarily by graduating students of the diurnal, trying to identify who would be these young school graduates and how they were experiencing this period of completion of basic education. Furthermore, not to be restricted to the questionnaire, nine interviews were conducted, six with graduating students and three with school teachers, as a possibility to enrich the analysis of this moment of completion of the school routine. The concepts used for that part of the work are: youths, consumer society, rites of passage and society of the spectacle. The results indicate that the graduation is not restricted only to ceremony, there are other events throughout the school year that are related with the graduation. Regarding the importance of this high school graduation for these young people, the answers were distinct. At the same time which could be a recognition by the student who is wrapping up a course of study and gaining a higher education than their families, there are others who consider it normal the completion of this stage. While most of the students wish to remain studying, others understand that this graduation may be the only of their lives, that is why the commitment to organize it in the best possible way.